A PTC composite material for heating plate and its preparation process
By introducing modified graphene and modified silica filler into PTC composites, the problem of poor PTC effect stability after heating and cooling cycle of polymer-based PTC materials is solved, and better flexibility and PTC effect stability are achieved. , suitable for the long-term stable heating needs of heating plates.
Patent Information
- Application Number
- CN202410242651.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-04
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-03-04
AI Technical Summary
After the number of heating and cooling cycles increases, existing polymer-based PTC materials are prone to problems such as increasing room temperature resistivity and decreasing PTC strength, resulting in poor stability of the PTC effect, which limits its application in heating sheets.
By introducing modified graphene and modified silica fillers into PTC composites, and through specific kneading processes and surface modification treatments, the flexibility and PTC effect stability of the composite materials are improved.
The PTC effect stability and flexibility of PTC composite material is significantly improved, the service life of the heating sheet is extended, and its performance stability during the hot and cold cycles is improved.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of PTC composite materials, and more specifically, to a PTC composite material for a heating plate and a preparation process thereof. Background Art
[0002] A heating sheet is a device that converts electrical energy into thermal energy by passing electricity through the surface of the material to make it heat up, and then transfers the thermal energy to the object to be heated. It is widely used in daily life, the automotive industry and production, such as electric kettles, electric ovens, electric blankets, electric floor heating films, car seat heaters, engine preheaters, etc. There are usually one or more heating elements on the surface of the heating sheet, and PTC is a semiconductor material or component with a positive temperature coefficient in the heating element.
[0003] PTC material is a conductive functional material with a positive temperature coefficient. Its conductive properties usually show a typical positive temperature coefficient effect, that is, the resistivity increases with the increase of temperature. PTC materials are usually divided into two categories: polymer-based PTC materials and ceramic-based PTC materials. Among them, polymer-based PTC materials are mixed with polymer matrix (such as polyethylene, polypropylene, etc.) and conductive fillers (such as carbon black, metal particles, etc.). Compared with ceramic-based PTC materials, polymer-based PTC materials have the characteristics of convenient processing and molding, low cost, light weight, good flexibility and low room temperature resistivity. However, as the number of heating and cooling cycles increases, polymer-based PTC materials are prone to increase in room temperature resistivity and decrease in PTC strength, which leads to poor stability of the PTC effect of polymer-based PTC materials, which is not conducive to the long-term stable heating of polymer-based PTC materials.
[0004] In addition, the polymer matrix and conductive filler in the polymer-based PTC material are usually rigid materials, which makes the polymer-based PTC material prepared by the composite of the polymer matrix and the conductive filler more rigid, which in turn leads to limited flexibility and ductility of the polymer-based PTC material, limiting the application scope of the polymer-based PTC material. Summary of the invention
[0005] In view of this, and in view of the deficiencies of the prior art, the present invention provides a PTC composite material for a heating plate and a preparation process thereof, which improves the stability of the PTC effect and the PTC strength and the flexibility of the PTC material.
[0006] A PTC composite material for a heating plate, characterized by comprising the following components:
[0007] Modified graphene and composite PTC material, wherein the mixing mass ratio of the modified graphene and the composite PTC material is (1-2): (3-5);
[0008] The modified graphene is obtained by acidifying the graphene with a mixture of a dilute nitric acid solution, concentrated nitric acid and concentrated sulfuric acid in sequence, and then modifying it with a titanate coupling agent;
[0009] The raw materials of the composite PTC material include: modified silica filler and composite intermediate, wherein the mass ratio of the modified silica filler and the composite intermediate is (1-5): (75-90);
[0010] The raw materials of the modified silica filler include: 4 to 8 parts by weight of fumed silica, 1 to 3 parts by weight of hexadecyltrimethylammonium bromide, and 50 to 75 parts by weight of deionized water;
[0011] The raw materials of the composite intermediate include: high-density polyethylene, compounded rubber, compounded masterbatch and ethylene-octene copolymer, wherein the mass ratio of the high-density polyethylene, compounded rubber, compounded masterbatch and ethylene-octene copolymer is (30-35): (5-10): (25-30): (12-20);
[0012] The raw materials of the rubber compound include: 100-120 parts by weight of EPDM raw rubber, 2-4 parts by weight of brominated p-tert-octylphenolic vulcanized resin, 1-3 parts by weight of stannous chloride dihydrate, 2-5 parts by weight of stearic acid and 1-2 parts by weight of paraffin wax;
[0013] The raw materials of the mixed masterbatch include: high-density polyethylene and carbon black, wherein the mass ratio of the high-density polyethylene to the carbon black is (1-3):1.
[0014] A preparation process of a PTC composite material for a heating plate comprises the following steps:
[0015] S1: Rubber mixing process,
[0016] The raw EPDM rubber is put into a double-roll open mill, and after several times of thin-pass plastication, rubber tapping and triangle packing, a mixed rubber material is obtained;
[0017] S2: Mixing of polymer matrix and conductive filler,
[0018] After high-density polyethylene and carbon black are mixed in proportion, they are extruded and granulated to obtain a mixed masterbatch, and the high-density polyethylene, the mixed rubber material, the mixed masterbatch and the ethylene-octene copolymer are mixed and fused to obtain a composite intermediate;
[0019] S3: Preparation and addition of modified silica filler,
[0020] Mix cetyltrimethylammonium bromide, deionized water and fumed silica, heat in a water bath for a period of time, filter out the residue, wash and dry the residue to obtain a modified silica filler, mix the modified silica filler with the composite intermediate to obtain a composite PTC material;
[0021] S4: Graphene grafting modification and doping mixing,
[0022] The graphene is added to a dilute nitric acid solution, heated in a water bath with stirring, and after the reaction is completed, the filter residue is filtered out and washed, and then the washed filter residue is added to a mixture of concentrated nitric acid and concentrated sulfuric acid, and heated in a water bath with stirring. After the reaction is completed, the filter residue is diluted, filtered out, and washed to obtain acidified graphene, and the graphene is added to an isopropanol solution of a titanate coupling agent, and after ball milling and drying, modified graphene is obtained, and the modified graphene is mixed and fused with a composite PTC material to obtain a flexible PTC composite material.
[0023] Preferably, the rubber mixing process in step S1 specifically comprises the following steps:
[0024] S1.1: 100-120 parts by weight of EPDM raw rubber is placed in a two-roll open mill, and the EPDM raw rubber is placed between the rollers. After the EPDM raw rubber passes between the rollers, it is not wrapped around the rollers and falls directly onto the rubber receiving plate. After all the EPDM raw rubber passes between the rollers, a thin pass plastication operation is completed, and then the EPDM raw rubber that has undergone the thin pass plastication operation is returned to between the rollers. The above thin pass plastication operation is repeated 3-6 times;
[0025] S1.2: Subsequently, 2 to 5 parts by mass of stearic acid, 1 to 2 parts by mass of paraffin wax, 1 to 3 parts by mass of stannous chloride dihydrate and 2 to 4 parts by mass of brominated p-tert-octylphenolic vulcanized resin are added to a two-roll mill to obtain a rubber compound. The rubber compound in the two-roll mill is rolled on the rollers 3 to 5 times, and then the rubber compound on the rollers is cut transversely. Then, the left and right sides of the rubber compound are folded alternately toward the middle, and the rubber compound is formed into a triangular rubber bag on the front roller. After all the rubber compound has passed the rollers, a triangular packing and mixing is completed, and then the corner after the triangular packing and mixing is inserted into the rollers. The above triangular packing and mixing operation is repeated 2 to 5 times;
[0026] S1.3: After the mixing is completed, the mixed rubber material is obtained, the roller spacing between the rollers is widened, and the mixed rubber material is discharged for standby use;
[0027] Preferably, step S2 of mixing the polymer matrix and the conductive filler comprises the following steps:
[0028] S2.1: adding high-density polyethylene and carbon black in a mass ratio of (1-3):1 to a high-speed mixer for premixing for 6-12 minutes at a speed of 3000-4000 rpm / min to obtain a premix. After the premixing is completed, the premix is extruded and granulated by an extruder to obtain a mixed masterbatch;
[0029] S2.2: Cut the mixed rubber into square sheets with a side length of 2 to 5 cm with scissors, put high-density polyethylene, the shredded mixed rubber, the mixed masterbatch and the ethylene-octene copolymer into a container for preliminary stirring and mixing, wherein the mass ratio of high-density polyethylene, the shredded mixed rubber, the mixed masterbatch and the ethylene-octene copolymer is (30 to 35): (5 to 10): (25 to 30): (12 to 20);
[0030] S2.3: Then, all the materials in the container are added to the torque rheometer, and mixed at a temperature of 150 to 160° C. for 10 to 15 minutes at a torque rheometer speed of 60 to 80 rpm / min to obtain a composite intermediate;
[0031] Preferably, step S3 of preparing and adding modified silica filler specifically comprises the following steps:
[0032] S3.1: Mix 1 to 3 parts by mass of cetyltrimethylammonium bromide and 10 to 15 parts by mass of deionized water, and stir evenly in a water bath at a temperature of 50 to 55° C. to obtain a reaction solution;
[0033] S3.2: Add 4 to 8 parts by mass of fumed silica to 40 to 60 parts by mass of deionized water, and disperse by ultrasonic for 20 to 30 minutes to obtain a silica suspension;
[0034] S3.3: Add the reaction solution to the silica suspension under a water bath condition at a temperature of 50 to 55°C, continue to stir at a uniform speed for 1.5 to 2h, and the stirring speed is 300 to 500rpm / min. After the reaction is completed, filter out the filter residue A, wash the filter residue A with deionized water for 3 to 5 times, and then put the washed filter residue A into a drying oven, and dry it at a temperature of 70 to 80°C for 50 to 60min to obtain a modified silica filler;
[0035] S3.4: Add the modified silica filler to the torque rheometer containing the composite intermediate, the mixing mass ratio of the modified silica filler and the composite intermediate is (1-5): (75-90), and mix at a temperature of 130-160° C. for 10-15 min at a speed of 60-80 rpm / min to obtain a composite PTC material;
[0036] Preferably, step S4 of graphene grafting modification and doping mixing specifically comprises the following steps:
[0037] S4.1: adding graphene to a dilute nitric acid solution with a concentration of 0.5 mol / L, with a solid-liquid ratio of 1:(10-15), stirring in a water bath at a temperature of 72-75°C for 20-24 hours, and after the reaction is completed, filtering the obtained mixed solution A to obtain a filter residue B, and washing the filter residue B with deionized water until the deionized water after the last washing is neutral;
[0038] S4.2: Add the cleaned filter residue B to a mixture of concentrated nitric acid and concentrated sulfuric acid, stir in a water bath at a temperature of 56 to 60°C for 20 to 24 hours to obtain a viscous mixed solution B, divide deionized water 3 to 5 times the volume of the mixed solution B into 4 to 6 portions and add them to the mixed solution B intermittently, stir each portion of deionized water for 3 to 5 minutes after adding it to the mixed solution B and let it stand for 30 to 40 minutes, and after the last portion of deionized water is added, stirred and left to stand, a diluted mixed solution B is obtained;
[0039] S4.3: Filter the diluted mixed solution B to obtain a filter residue C, and wash the filter residue C with deionized water until the deionized water after the last washing is neutral, thereby obtaining graphene after acidification;
[0040] S4.4: Add the titanate coupling agent to the isopropanol solution and stir evenly to obtain a reaction solution, then add the acidified graphene to the reaction solution, stir and mix to obtain a mixed solution C, and ball mill the mixed solution C for 60 to 80 minutes using a ball mill;
[0041] S4.5: After the ball milling is completed, the mixed solution C after ball milling is placed in a drying oven and dried at a temperature of 72 to 80° C. for 30 to 50 min to obtain modified graphene;
[0042] S4.6: Add the modified graphene to the torque rheometer containing the composite PTC material, the mixing mass ratio of the modified graphene and the composite PTC material is (1-2): (3-5), mix at a temperature of 130-160°C for 10-15 minutes, and a rotation speed of 60-80rpm / min to obtain a flexible PTC composite material.
[0043] Preferably, in step S1.1, the roller distance between the rollers is 0.6-1 mm.
[0044] Preferably, in step S1.3, the adjusted roller distance is 3 to 5 mm.
[0045] Preferably, in step S4.2, the mixed solution of concentrated nitric acid and concentrated sulfuric acid is prepared by mixing concentrated nitric acid with a concentration of 14 mol / L and concentrated sulfuric acid with a concentration of 18.4 mol / L in a volume ratio of 3:(1-2).
[0046] Preferably, in step S4.4, the mixing mass ratio of the titanate coupling agent to the isopropanol solution is (2-5):100.
[0047] The present invention has the following advantages:
[0048] 1. In the present invention, by mixing and fusing the mixed rubber material with high-density polyethylene, mixed masterbatch and ethylene-octene copolymer, a fine and stable rubber cross-linking network can be constructed inside the composite intermediate, and the ethylene-octene copolymer is added as a softening component to prepare a composite intermediate with good PTC effect stability and flexibility, which is beneficial to improve the PTC strength stability and mechanical properties of the composite PTC material.
[0049] 2. In the present invention, modified silica filler is introduced into the composite intermediate. Since cationic groups are adsorbed on the surface of the modified silica filler, the hydrophilicity and hydrophobicity of silica can be improved, thereby improving the affinity between silica and the composite intermediate, and improving the uniformity of the distribution of the modified silica filler and the composite intermediate mixture. In addition, the modified silica filler can reduce the number of carbon black aggregates in the composite PTC material, effectively limit the migration and rearrangement of carbon black in the composite PTC material during the hot and cold cycle, thereby constructing a more stable conductive network inside the composite PTC material, further improving the conductive network stability and PTC effect stability of the composite PTC material, and then when the composite PTC material is used in the heating plate, it is beneficial for the heating plate to maintain a stable heating effect for a long time.
[0050] 3. In the present invention, by performing surface grafting modification treatment on graphene and doping the modified graphene into the composite PTC material, the graphene reduces the electrical percolation threshold of the composite PTC material and further improves the tensile strength and PTC strength of the composite PTC material, thereby obtaining a flexible PTC composite material with good PTC strength and flexibility. DETAILED DESCRIPTION
[0051] In order to enable persons skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0052] Example 1
[0053] A preparation process of a PTC composite material for a heating plate, specifically comprising the following steps:
[0054] S1: Rubber mixing process
[0055] S1.1: 120 parts by mass of EPDM raw rubber are placed in a two-roll open mill, and the EPDM raw rubber is placed between the rollers. After the EPDM raw rubber passes between the rollers, it is not wrapped around the rollers and falls directly onto the rubber receiving plate. After all the EPDM raw rubber passes between the rollers, a thin pass plasticating operation is completed, and then the EPDM raw rubber that has undergone the thin pass plasticating operation is returned to between the rollers. The above thin pass plasticating operation is repeated 6 times, wherein the roller distance between the rollers is 1 mm;
[0056] S1.2: Subsequently, 5 parts by mass of stearic acid, 2 parts by mass of paraffin wax, 3 parts by mass of stannous chloride dihydrate and 4 parts by mass of brominated p-tert-octylphenolic vulcanized resin were added to a double-roll mill to obtain a rubber compound. The rubber compound in the double-roll mill was rolled on the rollers 5 times, and then the rubber compound on the rollers was cut transversely. Then, the left and right sides of the rubber compound were folded alternately toward the middle, and the rubber compound was formed into a triangular rubber bag on the front roller. After all the rubber compound was passed through the rollers, a triangular packing and mixing was completed, and then the corner after the triangular packing and mixing was inserted into the rollers. The above triangular packing and mixing operation was repeated 5 times to ensure mixing uniformity.
[0057] S1.3: After the mixing is completed, the mixed rubber is obtained, the roller distance between the rollers is adjusted to 5 mm, and the mixed rubber is discharged for standby use;
[0058] S2: Compounding of polymer matrix and conductive filler
[0059] S2.1: High-density polyethylene and carbon black were added to a high-speed mixer in a mass ratio of 3:1 and premixed for 12 minutes at a speed of 4000 rpm / min to obtain a premix. After the premixing was completed, the premix was extruded and granulated by an extruder to obtain a mixed masterbatch;
[0060] S2.2: Cut the mixed rubber into square sheets with a side length of 2 cm with scissors, put high-density polyethylene, the shredded mixed rubber, the mixed masterbatch and the ethylene-octene copolymer into a container for preliminary stirring and mixing, wherein the mass ratio of high-density polyethylene, the shredded mixed rubber, the mixed masterbatch and the ethylene-octene copolymer is 7:2:6:4;
[0061] S2.3: Then, all the materials in the container were added to the torque rheometer, mixed at a temperature of 160° C. for 15 min, and the speed of the torque rheometer was 80 rpm / min to obtain a composite intermediate;
[0062] S3: Preparation and addition of modified silica filler
[0063] S3.1: Mix 3 parts by mass of cetyltrimethylammonium bromide and 15 parts by mass of deionized water, and stir evenly in a water bath at a temperature of 55° C. to obtain a reaction solution;
[0064] S3.2: Add 8 parts by mass of fumed silica to 60 parts by mass of deionized water, and disperse by ultrasonic for 30 minutes to obtain a silica suspension;
[0065] S3.3: Add the reaction solution to the silica suspension under a water bath condition at a temperature of 55°C, continue to stir at a uniform speed for 2h, and the stirring speed is 500rpm / min. After the reaction is completed, filter out the filter residue A, wash the filter residue A with deionized water 5 times, and then put the washed filter residue A into a drying oven and dry it at a temperature of 80°C for 60min to obtain a modified silica filler;
[0066] S3.4: Add the modified silica filler to the torque rheometer containing the composite intermediate, the mixing mass ratio of the modified silica filler and the composite intermediate is 1:45, and mix at a temperature of 160° C. for 15 min at a speed of 80 rpm / min to obtain a composite PTC material;
[0067] S4: Graphene grafting modification and doping mixing
[0068] S4.1: adding graphene to a dilute nitric acid solution with a concentration of 0.5 mol / L, with a solid-liquid ratio of 1:15, stirring in a water bath at a temperature of 75°C for 24 hours, and after the reaction is completed, filtering the obtained mixed solution A to obtain a filter residue B, and washing the filter residue B with deionized water until the deionized water after the last washing is neutral;
[0069] S4.2: Add the cleaned filter residue B to a mixture of concentrated nitric acid and concentrated sulfuric acid, wherein the mixture of concentrated nitric acid and concentrated sulfuric acid is prepared by mixing 14 mol / L concentrated nitric acid and 18.4 mol / L concentrated sulfuric acid in a volume ratio of 3:2, and stir in a water bath at a temperature of 60°C for 24 hours to obtain a viscous mixed solution B, and divide deionized water whose volume is 5 times that of the mixed solution B into 6 portions and add them to the mixed solution B intermittently, and stir each portion of deionized water for 5 minutes after adding it to the mixed solution B and let it stand for 40 minutes, and after the last portion of deionized water is added, stirred and left to stand, a diluted mixed solution B is obtained;
[0070] S4.3: Filter the diluted mixed solution B to obtain a filter residue C, and wash the filter residue C with deionized water until the deionized water after the last washing is neutral, thereby obtaining graphene after acidification;
[0071] S4.4: adding a titanate coupling agent to an isopropanol solution and stirring evenly, wherein the mass ratio of the titanate coupling agent to the isopropanol solution is 5:100, to obtain a reaction solution, and then adding the acidified graphene to the reaction solution, stirring and mixing, to obtain a mixed solution C, and ball milling the mixed solution C with a ball mill for 80 min, so that the titanate coupling agent is evenly covered on the surface of the acidified graphene;
[0072] S4.5: After the ball milling is completed, the mixed solution C after ball milling is placed in a drying oven and dried at a temperature of 80° C. for 50 min to obtain modified graphene;
[0073] S4.6: Add the modified graphene to the torque rheometer containing the composite PTC material, the mixing mass ratio of the modified graphene and the composite PTC material is 2:5, mix at a temperature of 160°C for 15 minutes, and a rotation speed of 80 rpm / min to obtain a flexible PTC composite material.
[0074] Example 2
[0075] A preparation process of a PTC composite material for a heating plate, specifically comprising the following steps:
[0076] S1: Rubber mixing process
[0077] S1.1: 120 parts by mass of EPDM raw rubber are placed in a two-roll open mill, and the EPDM raw rubber is placed between the rollers. After the EPDM raw rubber passes between the rollers, it falls directly onto the rubber receiving plate without being wrapped by the rollers. After all the EPDM raw rubber passes between the rollers, a thin pass plasticating operation is completed, and then the EPDM raw rubber that has undergone the thin pass plasticating operation is returned to between the rollers. The above-mentioned thin pass plasticating operation is repeated 3 times, wherein the roller distance between the rollers is 0.6 mm;
[0078] S1.2: Subsequently, 5 parts by mass of stearic acid, 2 parts by mass of paraffin wax, 3 parts by mass of stannous chloride dihydrate and 4 parts by mass of brominated p-tert-octylphenolic vulcanized resin were added to a double-roll mill to obtain a rubber compound. The rubber compound in the double-roll mill was rolled on the rollers for 3 times, and then the rubber compound on the rollers was cut transversely. Then, the left and right sides of the rubber compound were folded alternately toward the middle, and the rubber compound was formed into a triangular rubber bag on the front roller. After all the rubber compound was passed through the rollers, a triangular packing and mixing was completed, and then the corner after the triangular packing and mixing was inserted into the rollers. The above triangular packing and mixing operation was repeated 2 times to ensure mixing uniformity.
[0079] S1.3: After the mixing is completed, the mixed rubber is obtained, the roller distance between the rollers is adjusted to 3mm, and the mixed rubber is discharged for standby use;
[0080] S2: Compounding of polymer matrix and conductive filler
[0081] S2.1: High-density polyethylene and carbon black were added to a high-speed mixer in a mass ratio of 3:1 and premixed for 6 minutes at a speed of 3000 rpm / min to obtain a premix. After the premixing was completed, the premix was extruded and granulated by an extruder to obtain a mixed masterbatch;
[0082] S2.2: Cut the mixed rubber into square sheets with a side length of 5 cm with scissors, put high-density polyethylene, the shredded mixed rubber, the mixed masterbatch and the ethylene-octene copolymer into a container for preliminary stirring and mixing, wherein the mass ratio of high-density polyethylene, the shredded mixed rubber, the mixed masterbatch and the ethylene-octene copolymer is 7:2:6:4;
[0083] S2.3: Then, all the materials in the container were added to the torque rheometer, mixed at a temperature of 150° C. for 15 min, and the speed of the torque rheometer was 60 rpm / min to obtain a composite intermediate;
[0084] S3: Preparation and addition of modified silica filler
[0085] S3.1: Mix 3 parts by mass of cetyltrimethylammonium bromide and 15 parts by mass of deionized water, and stir evenly in a water bath at a temperature of 50° C. to obtain a reaction solution;
[0086] S3.2: Add 8 parts by mass of fumed silica to 60 parts by mass of deionized water, and disperse by ultrasonic for 20 minutes to obtain a silica suspension;
[0087] S3.3: Add the reaction solution to the silica suspension under a water bath condition at a temperature of 50°C, continue to stir at a uniform speed for 1.5h, and the stirring speed is 300rpm / min. After the reaction is completed, filter out the filter residue A, wash the filter residue A with deionized water for 3 times, and then put the washed filter residue A into a drying oven and dry it at a temperature of 70°C for 50min to obtain a modified silica filler;
[0088] S3.4: Add the modified silica filler to the torque rheometer containing the composite intermediate, the mixing mass ratio of the modified silica filler and the composite intermediate is 1:45, and mix at a temperature of 130° C. for 10 min at a speed of 60 rpm / min to obtain a composite PTC material;
[0089] S4: Graphene grafting modification and doping mixing
[0090] S4.1: adding graphene to a dilute nitric acid solution with a concentration of 0.5 mol / L, with a solid-liquid ratio of 1:15, stirring in a water bath at a temperature of 72°C for 20 hours, and after the reaction is completed, filtering the obtained mixed solution A to obtain a filter residue B, and washing the filter residue B with deionized water until the deionized water after the last washing is neutral;
[0091] S4.2: Add the cleaned filter residue B to a mixture of concentrated nitric acid and concentrated sulfuric acid, wherein the mixture of concentrated nitric acid and concentrated sulfuric acid is prepared by mixing 14 mol / L concentrated nitric acid and 18.4 mol / L concentrated sulfuric acid in a volume ratio of 3:2, and stir in a water bath at a temperature of 56°C for 20 hours to obtain a viscous mixed solution B, and divide deionized water 5 times the volume of the mixed solution B into 6 portions and add them to the mixed solution B intermittently, and stir each portion of deionized water for 3 minutes after adding it to the mixed solution B and let it stand for 30 minutes. After the last portion of deionized water is added, stirred and left to stand, a diluted mixed solution B is obtained;
[0092] S4.3: Filter the diluted mixed solution B to obtain a filter residue C, and wash the filter residue C with deionized water until the deionized water after the last washing is neutral, thereby obtaining graphene after acidification;
[0093] S4.4: adding a titanate coupling agent to an isopropanol solution and stirring evenly, the mass ratio of the titanate coupling agent to the isopropanol solution is 5:100, to obtain a reaction solution, and then adding the acidified graphene to the reaction solution, stirring and mixing, to obtain a mixed solution C, and ball milling the mixed solution C with a ball mill for 60 minutes, so that the titanate coupling agent is evenly covered on the surface of the acidified graphene;
[0094] S4.5: After the ball milling is completed, the mixed solution C after ball milling is placed in a drying oven and dried at 72° C. for 30 min to obtain modified graphene;
[0095] S4.6: Add the modified graphene to the torque rheometer containing the composite PTC material, the mixing mass ratio of the modified graphene and the composite PTC material is 2:5, mix at a temperature of 130°C for 10 minutes and a rotation speed of 60 rpm / min to obtain a flexible PTC composite material.
[0096] Example 3
[0097] A preparation process of a PTC composite material for a heating plate, specifically comprising the following steps:
[0098] S1: Rubber mixing process
[0099] S1.1: 100 parts by mass of EPDM raw rubber are put into a two-roll open mill, and the EPDM raw rubber is put between the rollers. After the EPDM raw rubber passes between the rollers, it falls directly onto the rubber receiving plate without being wrapped by the rollers. After all the EPDM raw rubber passes between the rollers, a thin pass plasticating operation is completed, and then the EPDM raw rubber that has undergone the thin pass plasticating operation is returned to between the rollers. The above-mentioned thin pass plasticating operation is repeated 6 times, wherein the roller distance between the rollers is 1 mm;
[0100] S1.2: Subsequently, 2 parts by mass of stearic acid, 1 part by mass of paraffin wax, 1 part by mass of stannous chloride dihydrate and 2 parts by mass of brominated p-tert-octylphenolic vulcanized resin were added to a double-roll mill to obtain a rubber compound. The rubber compound in the double-roll mill was rolled on the rollers 5 times, and then the rubber compound on the rollers was cut transversely. Then, the left and right sides of the rubber compound were folded alternately toward the middle, and the rubber compound was formed into a triangular rubber bag on the front roller. After all the rubber compound was passed through the rollers, a triangular packing and mixing was completed, and then the corner after the triangular packing and mixing was inserted into the rollers. The above triangular packing and mixing operation was repeated 5 times to ensure mixing uniformity.
[0101] S1.3: After the mixing is completed, the mixed rubber is obtained, the roller distance between the rollers is adjusted to 5 mm, and the mixed rubber is discharged for standby use;
[0102] S2: Compounding of polymer matrix and conductive filler
[0103] S2.1: High-density polyethylene and carbon black were added to a high-speed mixer in a mass ratio of 1:1 and premixed for 12 minutes at a speed of 4000 rpm / min to obtain a premix. After the premixing was completed, the premix was extruded and granulated by an extruder to obtain a mixed masterbatch;
[0104] S2.2: Cut the mixed rubber into square sheets with a side length of 2 cm with scissors, put high-density polyethylene, the shredded mixed rubber, the mixed masterbatch and the ethylene-octene copolymer into a container for preliminary stirring and mixing, wherein the mass ratio of high-density polyethylene, the shredded mixed rubber, the mixed masterbatch and the ethylene-octene copolymer is 30:5:25:12;
[0105] S2.3: Then, all the materials in the container were added to the torque rheometer, mixed at a temperature of 160° C. for 15 min, and the speed of the torque rheometer was 80 rpm / min to obtain a composite intermediate;
[0106] S3: Preparation and addition of modified silica filler
[0107] S3.1: Mix 1 part by mass of cetyltrimethylammonium bromide and 10 parts by mass of deionized water, and stir evenly in a water bath at a temperature of 55° C. to obtain a reaction solution;
[0108] S3.2: Add 4 parts by mass of fumed silica to 40 parts by mass of deionized water, and disperse by ultrasonic for 30 minutes to obtain a silica suspension;
[0109] S3.3: Add the reaction solution to the silica suspension under a water bath condition at a temperature of 55°C, continue to stir at a uniform speed for 2h, and the stirring speed is 500rpm / min. After the reaction is completed, filter out the filter residue A, wash the filter residue A with deionized water 5 times, and then put the washed filter residue A into a drying oven and dry it at a temperature of 80°C for 60min to obtain a modified silica filler;
[0110] S3.4: Add the modified silica filler to the torque rheometer containing the composite intermediate, the mixing mass ratio of the modified silica filler and the composite intermediate is 1:75, and mix at a temperature of 160° C. for 15 min at a speed of 80 rpm / min to obtain a composite PTC material;
[0111] S4: Graphene grafting modification and doping mixing
[0112] S4.1: adding graphene to a dilute nitric acid solution with a concentration of 0.5 mol / L, with a solid-liquid ratio of 1:10, stirring in a water bath at a temperature of 75°C for 24 hours, and after the reaction is completed, filtering the obtained mixed solution A to obtain a filter residue B, and washing the filter residue B with deionized water until the deionized water after the last washing is neutral;
[0113] S4.2: Add the cleaned filter residue B to a mixture of concentrated nitric acid and concentrated sulfuric acid, wherein the mixture of concentrated nitric acid and concentrated sulfuric acid is prepared by mixing 14 mol / L concentrated nitric acid and 18.4 mol / L concentrated sulfuric acid in a volume ratio of 3:1, and stir in a water bath at a temperature of 60°C for 24 hours to obtain a viscous mixed solution B, and divide deionized water having a volume three times that of the mixed solution B into 4 equal portions and add them to the mixed solution B intermittently, and stir each portion of deionized water for 5 minutes after adding it to the mixed solution B and let it stand for 40 minutes, and after the last portion of deionized water is added, stirred and left to stand, a diluted mixed solution B is obtained;
[0114] S4.3: Filter the diluted mixed solution B to obtain a filter residue C, and wash the filter residue C with deionized water until the deionized water after the last washing is neutral, thereby obtaining graphene after acidification;
[0115] S4.4: adding a titanate coupling agent to the isopropanol solution and stirring evenly, the mass ratio of the titanate coupling agent to the isopropanol solution is 2:100, to obtain a reaction solution, and then adding the acidified graphene to the reaction solution, stirring and mixing, to obtain a mixed solution C, and ball milling the mixed solution C with a ball mill for 80 minutes, so that the titanate coupling agent is evenly covered on the surface of the acidified graphene;
[0116] S4.5: After the ball milling is completed, the mixed solution C after ball milling is placed in a drying oven and dried at a temperature of 80° C. for 50 min to obtain modified graphene;
[0117] S4.6: Add the modified graphene to the torque rheometer containing the composite PTC material, the mixing mass ratio of the modified graphene and the composite PTC material is 1:3, mix at a temperature of 160°C for 15 minutes, and a rotation speed of 80 rpm / min to obtain a flexible PTC composite material.
[0118] Comparative Example 1
[0119] Compared with Example 1, the difference of Comparative Example 1 is that the step of adding ethylene-octene copolymer in step S2.2 is removed, and the other steps remain unchanged to prepare a flexible PTC composite material, which is recorded as Comparative Example 1.
[0120] Comparative Example 2
[0121] Compared with Example 1, the difference of Comparative Example 2 is that the preparation and addition of the modified silica filler in step S3 are removed, and the other steps remain unchanged, and a flexible PTC composite material is prepared, which is recorded as Comparative Example 2.
[0122] Comparative Example 3
[0123] Compared with Example 1, the difference of Comparative Example 3 is that the graphene grafting modification and doping mixing in step S4 are removed, and the other steps remain unchanged to prepare a composite PTC material, which is recorded as Comparative Example 3.
[0124] The flexible PTC composite materials / composite PTC materials prepared in Examples 1-3 and Comparative Examples 1-3 were placed in molds respectively, and the molds were placed in a hot pressing molding machine, preheated at 150°C for 3 minutes, and then hot pressed at a pressure of 12 MPa and a temperature of 180°C for 10 minutes. After the hot pressing, cold pressed to room temperature at a pressure of 12 MPa to obtain test samples with a thickness of 1.5 mm and a side length of 50 mm.
[0125] According to Examples 1-3 and Comparative Examples 1 and 3, three test samples were taken from each group. The test samples were subjected to a tensile strength test using a universal material testing machine at a tensile speed of 20 mm / min. The tensile strength and elongation at break were measured, and the results were averaged. The results are shown in Table 1.
[0126] Tensile strength(Mpa) Elongation at break (%) Example 1 27.45 300.35 Example 2 26.83 298.92 Example 3 27.03 296.26 Comparative Example 1 9.81 21.47 Comparative Example 3 18.93 261.59
[0127] Table 1
[0128] As can be seen from Table 1, the tensile strength and elongation at break of the flexible PTC composite materials prepared in Examples 1-3 are greater than the test results of the flexible PTC composite materials / composite PTC materials in Comparative Examples 1 and 3, indicating that the addition of ethylene-octene copolymer and modified graphene can effectively improve the mechanical properties of the flexible PTC composite materials and enhance the flexibility of the flexible PTC composite materials.
[0129] The samples were grouped according to Examples 1-3 and Comparative Examples 1-3, and one test sample was taken from each group. The test samples were placed in a constant temperature heating box, and a heating and cooling cycle was performed on the test samples, so that the test samples were heated to 120°C at a heating rate of 5°C / min, and then naturally cooled to 20°C, and the cycle was repeated 3 times in total. The PTC strength of the test samples after cooling to 20°C was tested each time. The PTC strength is the logarithm of the ratio of the maximum resistivity to the room temperature resistivity. The PTC strength of each group of test samples was obtained. The results are shown in Table 2.
[0130] Initial PTC strength PTC strength after one hot and cold cycle PTC strength after 2 hot and cold cycles PTC strength after 3 hot and cold cycles Example 1 9.52 9.47 9.44 9.27 Example 2 9.31 9.24 9.18 9.12 Example 3 9.44 9.38 9.31 9.23 Comparative Example 1 7.93 7.57 7.04 6.74 Comparative Example 2 7.02 6.89 6.25 5.36 Comparative Example 3 7.35 7.11 6.69 6.07
[0131] Table 2
[0132] As can be seen from Table 2, the initial PTC strength of the flexible PTC composite materials prepared in Examples 1-3 is greater than the initial PTC strength of the flexible PTC composite materials / composite PTC materials in Comparative Examples 1-3, indicating that the addition of ethylene-octene copolymer, modified silica filler and modified graphene can effectively improve the PTC strength of the flexible PTC composite material, and further, when the flexible PTC composite material is used in a heating plate, it is beneficial to improve the temperature sensitivity of the heating plate.
[0133] Moreover, after three heating and cooling cycles, the PTC strength of the flexible PTC composite materials obtained in Examples 1-3 did not change significantly, while the PTC strength of the flexible PTC composite materials / composite PTC materials in Comparative Examples 1-3 decreased significantly after three heating and cooling cycles, indicating that the addition of ethylene-octene copolymer, modified silica filler and modified graphene can effectively improve the PTC effect stability of the flexible PTC composite materials, among which the modified silica filler has a more significant effect on the PTC effect stability of the flexible PTC composite materials. Therefore, when the flexible PTC composite materials are used in the heating plate, it is beneficial for the heating plate to maintain a stable heating effect for a long time.
[0134] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all such improvements and changes should fall within the scope of protection of the appended claims of the present invention. Parts not described in detail in this specification belong to the prior art known to those skilled in the art.
Claims
1. A PTC composite material for a heating plate, characterized in that: Includes the following ingredients: Modified graphene and composite PTC material, wherein the mixing mass ratio of the modified graphene and the composite PTC material is (1-2): (3-5); The modified graphene is obtained by acidifying the graphene with a mixture of a dilute nitric acid solution, concentrated nitric acid and concentrated sulfuric acid in sequence, and then modifying it with a titanate coupling agent; The raw materials of the composite PTC material include: modified silica filler and composite intermediate, wherein the mass ratio of the modified silica filler and the composite intermediate is (1-5): (75-90); The raw materials of the modified silica filler include: 4 to 8 parts by weight of fumed silica, 1 to 3 parts by weight of hexadecyltrimethylammonium bromide, and 50 to 75 parts by weight of deionized water; The raw materials of the composite intermediate include: high-density polyethylene, compounded rubber, compounded masterbatch and ethylene-octene copolymer, wherein the mass ratio of high-density polyethylene, compounded rubber, compounded masterbatch and ethylene-octene copolymer is (30-35): (5-10): (25-30): (12-20); The raw materials of the rubber compound include: 100-120 parts by weight of EPDM raw rubber, 2-4 parts by weight of brominated p-tert-octylphenolic vulcanized resin, 1-3 parts by weight of stannous chloride dihydrate, 2-5 parts by weight of stearic acid and 1-2 parts by weight of paraffin wax; The raw materials of the mixed masterbatch include: high-density polyethylene and carbon black, wherein the mass ratio of high-density polyethylene to carbon black is (1-3):1; The PTC composite material for the heating plate is prepared according to the following steps: S1: Rubber mixing process, The EPDM raw rubber and the additives are put into a double-roll open mill, and after several times of thin-pass plastication, rubber tapping and triangle packing, a mixed rubber material is obtained; S2: Mixing of polymer matrix and conductive filler, After high-density polyethylene and carbon black are mixed in proportion, they are extruded and granulated to obtain a mixed masterbatch, and the high-density polyethylene, the mixed rubber material, the mixed masterbatch and the ethylene-octene copolymer are mixed and fused to obtain a composite intermediate; S3: Preparation and addition of modified silica filler, Mix cetyltrimethylammonium bromide, deionized water and fumed silica, heat in a water bath for a period of time, filter out the residue, wash and dry the residue to obtain a modified silica filler, mix the modified silica filler with the composite intermediate to obtain a composite PTC material; S4: Graphene grafting modification and doping mixing, The graphene is added to a dilute nitric acid solution, heated in a water bath with stirring, and after the reaction is completed, the filter residue is filtered out and washed, and then the washed filter residue is added to a mixture of concentrated nitric acid and concentrated sulfuric acid, heated in a water bath with stirring, and after the reaction is completed, the filter residue is diluted, filtered out, and washed to obtain acidified graphene, and the acidified graphene is added to an isopropanol solution of a titanate coupling agent, ball milled, and dried to obtain modified graphene, and the modified graphene is mixed and fused with a composite PTC material to obtain a flexible PTC composite material.
2. The PTC composite material for a heating sheet according to claim 1, characterized in that: Step S1 rubber mixing process specifically includes the following steps: S1.1: 100-120 parts by weight of EPDM raw rubber is placed in a two-roll open mill, and the EPDM raw rubber is placed between the rollers. After the EPDM raw rubber passes between the rollers, it is not wrapped around the rollers and falls directly onto the rubber receiving plate. After all the EPDM raw rubber passes between the rollers, a thin pass plastication operation is completed, and then the EPDM raw rubber that has undergone the thin pass plastication operation is returned to between the rollers. The above thin pass plastication operation is repeated 3-6 times; S1.2: Subsequently, 2 to 5 parts by mass of stearic acid, 1 to 2 parts by mass of paraffin wax, 1 to 3 parts by mass of stannous chloride dihydrate and 2 to 4 parts by mass of brominated p-tert-octylphenolic vulcanized resin are added to a two-roll mill to obtain a rubber compound. The rubber compound in the two-roll mill is rolled on the rollers 3 to 5 times, and then the rubber compound on the rollers is cut transversely, and then the left and right sides of the rubber compound are folded alternately toward the middle, and the rubber compound is formed into a triangular rubber bag on the front roller. After all the rubber compound has passed the rollers, a triangular packing and mixing is completed, and then the rubber compound after the triangular packing and mixing is inserted into the rollers, and the above triangular packing and mixing operation is repeated 2 to 5 times; S1.3: After the mixing is completed, the mixed rubber material is obtained, the roller distance between the rollers is widened, and the mixed rubber material is discharged for use.
3. The PTC composite material for a heating sheet according to claim 2, characterized in that: Step S2: mixing the polymer matrix and the conductive filler, specifically comprising the following steps: S2.1: adding high-density polyethylene and carbon black in a mass ratio of (1-3):1 into a high-speed mixer and premixing for 6-12 minutes at a speed of 3000-4000 rpm / min to obtain a premix. After the premixing is completed, the premix is extruded and granulated by an extruder to obtain a mixed masterbatch; S2.2: Cut the mixed rubber into square sheets with a side length of 2 to 5 cm with scissors, put high-density polyethylene, the chopped mixed rubber, the mixed masterbatch and the ethylene-octene copolymer into a container for preliminary stirring and mixing, wherein the mass ratio of high-density polyethylene, the chopped mixed rubber, the mixed masterbatch and the ethylene-octene copolymer is (30 to 35): (5 to 10): (25 to 30): (12 to 20); S2.3: Subsequently, all the materials in the container are added to the torque rheometer, and kneaded at a temperature of 150 to 160° C. for 10 to 15 minutes at a torque rheometer speed of 60 to 80 rpm / min to obtain a composite intermediate.
4. The PTC composite material for a heating sheet according to claim 3, characterized in that: Step S3: Preparation and addition of modified silica filler, specifically comprising the following steps: S3.1: Mix 1 to 3 parts by mass of cetyltrimethylammonium bromide and 10 to 15 parts by mass of deionized water, and stir evenly in a water bath at a temperature of 50 to 55° C. to obtain a reaction solution; S3.2: Add 4 to 8 parts by mass of fumed silica to 40 to 60 parts by mass of deionized water, and disperse by ultrasonic for 20 to 30 minutes to obtain a silica suspension; S3.3: Add the reaction solution to the silica suspension under a water bath condition at a temperature of 50 to 55°C, continue to stir at a uniform speed for 1.5 to 2h, and the stirring speed is 300 to 500rpm / min. After the reaction is completed, filter out the filter residue A, wash the filter residue A with deionized water for 3 to 5 times, and then put the washed filter residue A into a drying oven, and dry it at a temperature of 70 to 80°C for 50 to 60min to obtain a modified silica filler; S3.4: Add the modified silica filler to the torque rheometer containing the composite intermediate, the mixing mass ratio of the modified silica filler and the composite intermediate is (1-5): (75-90), mix at a temperature of 130-160°C for 10-15 minutes and a rotation speed of 60-80 rpm / min to obtain a composite PTC material.
5. The PTC composite material for a heating sheet according to claim 4, characterized in that: Step S4: graphene grafting modification and doping mixing, specifically comprising the following steps: S4.1: Add graphene to a dilute nitric acid solution with a concentration of 0.5 mol / L, with a solid-liquid ratio of 1:(10-15), and stir in a water bath at a temperature of 72-75°C for 20-24 hours. After the reaction is completed, the obtained mixed solution A is filtered to obtain a filter residue B, and the filter residue B is washed with deionized water until the deionized water after the last washing is neutral; S4.2: Add the cleaned filter residue B to a mixture of concentrated nitric acid and concentrated sulfuric acid, stir in a water bath at a temperature of 56 to 60°C for 20 to 24 hours to obtain a viscous mixed solution B, divide deionized water 3 to 5 times the volume of the mixed solution B into 4 to 6 portions and add them to the mixed solution B intermittently, stir each portion of deionized water for 3 to 5 minutes after adding it to the mixed solution B and let it stand for 30 to 40 minutes, and after the last portion of deionized water is added, stirred and left to stand, a diluted mixed solution B is obtained; S4.3: Filter the diluted mixed solution B to obtain a filter residue C, and wash the filter residue C with deionized water until the deionized water after the last washing is neutral, thereby obtaining graphene after acidification; S4.4: Add the titanate coupling agent to the isopropanol solution and stir evenly to obtain a reaction solution, then add the acidified graphene to the reaction solution, stir and mix to obtain a mixed solution C, and ball mill the mixed solution C for 60 to 80 minutes using a ball mill; S4.5: After the ball milling is completed, the mixed solution C after ball milling is placed in a drying oven and dried at a temperature of 72 to 80° C. for 30 to 50 min to obtain modified graphene; S4.6: Add the modified graphene to the torque rheometer containing the composite PTC material, the mixing mass ratio of the modified graphene and the composite PTC material is (1-2): (3-5), mix at a temperature of 130-160°C for 10-15 minutes and a rotation speed of 60-80 rpm / min to obtain a flexible PTC composite material.
6. The PTC composite material for a heating sheet according to claim 2, characterized in that: In step S1.1, the roller distance between the rollers is 0.6-1 mm.
7. The PTC composite material for a heating sheet according to claim 2, characterized in that: In step S1.3, the roller distance after adjustment is 3 to 5 mm.
8. The PTC composite material for a heating sheet according to claim 5, characterized in that: In step S4.2, the mixed solution of concentrated nitric acid and concentrated sulfuric acid is prepared by mixing concentrated nitric acid with a concentration of 14 mol / L and concentrated sulfuric acid with a concentration of 18.4 mol / L in a volume ratio of 3:(1-2).
9. The PTC composite material for a heating sheet according to claim 5, characterized in that: In step S4.4, the mixing mass ratio of the titanate coupling agent to the isopropanol solution is (2-5):100.
Citation Information
Patent Citations
Method for producing a semiconductor ceramic material, semiconductor ceramic material and a semiconductor component
CN103688319A
Polymer positive temperature coefficient (PTC) composite material containing graphene and carbon nanotubes, and preparation method of polymer PTC composite material
CN107602987A